HUBUNGAN PERHATIAN GURU DENGAN MINAT BELAJAR SISWA KELAS 3 SD INPRES 23 PASIR PUTIH KABUPATEN SORONG SELATAN - Wilhelmina Lokden; Nursalim; Lestari; Ribut Purwojuwono (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the relationship between teacher attention and learning interest among third-grade students at SD Inpres 23 Pasir Putih, South Sorong. The research problem stems from the lack of studies examining the impact of teacher attention on learning motivation in rural schools, despite its recognized importance in the learning process. A quantitative correlational approach was employed, with a total sampling of 16 students. Data were collected using a 4-point Likert scale questionnaire, validated for content and reliability (α=0.72). The results showed an average score of 63.43 (good category) for teacher attention and 66.12 (good category) for s tudent learning interest. However, Pearson Product Moment correlation analysis yielded a coefficient of r=0.084 (p>0.05), indicating no significant relationship between the two variables. These findings suggest that in rural school environments, other factors such as family support or learning facilities may play a more substantial role in student engagement. This study contributes to the development of teaching strategies in remote areas by advocating for a holistic approach involving multiple stakeholders.